2004
DOI: 10.1021/jf040078p
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Distribution during the Development of Leaves, Flowers, Stems, and Roots ofRosmarinus officinalis. Postulation of a Biosynthetic Pathway

Abstract: The distribution of seven flavonoids, eriocitrin, luteolin 3'-O-beta-d-glucuronide, hesperidin, diosmin, isoscutellarein 7-O-glucoside, hispidulin 7-O-glucoside, and genkwanin, has been studied in Rosmarinus officinalis leaves, flowers, stems, and roots during plant growth. The maximum level reached by luteolin 3'-O-beta-d-glucuronide in leaves during June-August suggests the existence of a delay between the activation of the enzymes involved in the flavanone and flavone biosynthesis. The presence of hesperidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(55 citation statements)
references
References 30 publications
2
53
0
Order By: Relevance
“…Isosakuranetin is also reported to be biosynthesized from naringenin via an O -methyltransferase enzyme expressed in E. coli [68]. Luteolin’s biosynthesis in Rosmarinus officinalis has been postulated by del Bano et al [69]. In this work, naringenin was proposed to be hydroxylated to eriodictyol and finally converted to luteolin by the enzyme flavone synthase.…”
Section: Discussionmentioning
confidence: 91%
“…Isosakuranetin is also reported to be biosynthesized from naringenin via an O -methyltransferase enzyme expressed in E. coli [68]. Luteolin’s biosynthesis in Rosmarinus officinalis has been postulated by del Bano et al [69]. In this work, naringenin was proposed to be hydroxylated to eriodictyol and finally converted to luteolin by the enzyme flavone synthase.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, this part of the plant has a higher antioxidant activity. Many reports have suggested that in the leaves, the stress level is high; for this reason more pigments quantity are generated, and this protects the leaf tissues from photochemical damage (del Baño et al 2004;Chew et al 2009). …”
Section: Antioxidant Activitymentioning
confidence: 99%
“…As this process is able to trigger the production of highly reactive chemical species at a cellular level, the leaf tissues are responsible for the generation of highly effective antioxidants that are capable of eliminating free radicals and minimizing oxidative damage (del Baño et al 2004;Chew et al 2009). …”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…This glycosylated flavonoid is found in citrus, hyssop, and rosemary and is commonly used for its venotonic effects [57][58][59]. In Europe, it is prescribed for treatment of venous insufficiency while in the US, it is marketed as a food supplement [60,61].…”
Section: Diosminmentioning
confidence: 99%